Hubungan Intellectual Capital dengan Kinerja Perusahaan Farmasi - Sabaruddinsah, Sabaruddinsah; Asiah, Neng (DPPM Universitas Pelita Bangsa, 2022)
The objectives of this study are to analyze the impact of intellectual capital on company’s financial performance-Return on Assets (ROA), Return on Equity (ROE) and Earning per Share (EPS); to identify the use of the concept of input-process-output of innovation capacity, the efficiency of operating processes, customer relationships are maintained, value-added human, on the firm’s performance.This research used pharmaceutical company data that listed in Indonesi Stock Exchange (IDX) 2014-2021. The model that used to measure intellectual capital was Partial Least Square (PLS) approach, a structural equation model (SEM)-based components or variants and alternative approaches are shifting from a SEM-based covariance to variant approach. The findings show that: (1) innovative capacity has a positive correlation with maintainable customer relationship; (2) innovative capacity has a positive correlation with human value added; (3) efficient operating processes has a positive correlation with maintainable customer relationship; (4) human value added has a positive correlation with maintainable customer relationship; (5) maintainable customer relationship has a positive correlation with corporate performance; and (6) human value added has a positive correlation with corporate performance.